Digitalisasi Ruang Hidup Pesisir: Pemetaan Potensi dan Edukasi Infrastruktur Berbasis Komunitas di Kecamatan Mantang: Digitalization of Coastal Living Spaces: Community-Based Mapping of Potentials and Infrastructure Education in Mantang District - Muhamad Zulfakar; Nola Ritha; Henky Irawan; Dian Kharisma Dewi; Dea Rizky Saputri; Aria Bagiasa Chidmahdjati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Mantang district is a coastal area with various local resources and infrastructure that need to be systematically documented as a foundation for village development planning. To date, the villages in this area lack structured spatial data to support evidence-based planning processes. This community service program aims to produce digital thematic maps and spatial information media that can be utilized by village governments and schools for territorial management and educational activities. The implementation methods include coordination with partners, secondary data collection, field observations by the PKM team, and digital processing and mapping using mapping software. This program produced several key outputs, including coastal potential maps, basic village infrastructure maps, accessibility maps, and educational infographics compiled from field data and geospatial processing. All outputs have been handed over to the village government, the district office, and local schools as supporting materials for planning, documentation, and learning. The results indicate that digital mapping conducted by the PKM team is able to provide accurate, comprehensive, and user-friendly spatial information to support capacity strengthening in spatial planning within the Mantang district.